Peningkatan Motivasi dan hasil Belajar Siswa Melalui Model Pembelajaran Kooperatif Two Stay Two Stray - Sukri Sukri (Universitas Negeri Padang, 2019)
Research is motivated by the lack of motivation and learning outcomes in the learning process. The use of appropriate learning models can increase motivation and student learning outcomes in XI-IPS High School Superior State Dharmasraya. Based on these problems the researchers applied the Two Stay Two Stray cooperative learning model with the aim of increasing student motivation and learning outcomes in economic subjects. This research method is a classroom action research conducted in two cycles and each cycle there are three meetings. Conducting research with the Two Stay Two Stray cooperative learning model on economic subjects includes (1) planning, (2) implementation, (3) observation, and (4) reflection. The results of this study indicate that the application of the Two Stay Two Stray cooperative learning model can increase motivation and learning outcomes of students of class XI IPS SMAN Unggul Dharmasraya. This is seen from the aspect of student motivation in cycle I and cycle II which increased by 17.6% and in the cognitive spec or learning outcomes in cycle I and cycle II also increased by 12%, although the increase was not too sharp but recruiting researchers this shows that the application of the Two Stay Two Stray cooperative learning model can be used to increase student motivation and learning outcomes in economic subjects.